2015
DOI: 10.3390/ijms16046677
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA MALAT-1 Enhances Stem Cell-Like Phenotypes in Pancreatic Cancer Cells

Abstract: Cancer stem cells (CSCs) play a vital role in tumor initiation, progression, metastasis, chemoresistance, and recurrence. The mechanisms that maintain the stemness of these cells remain largely unknown. Our previous study indicated that MALAT-1 may serve as an oncogenic long noncoding RNA in pancreatic cancer by promoting epithelial-mesenchymal transition (EMT) and regulating CSCs markers expression. More significantly, there is emerging evidence that the EMT process may give rise to CSCs, or at least cells wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
129
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(132 citation statements)
references
References 55 publications
(59 reference statements)
1
129
1
Order By: Relevance
“…MALAT has been found to be highly overexpressed in several human malignancies and has been associated with tumor invasion and metastasis in various cancers. [78][79][80][81][82][83][84] Jiao et al 78 reported that MALAT1 could increase the proportion of pancreatic CSCs, maintain self-renewal capacity, decrease chemosensitivity to anticancer drugs and promote angiogenesis in vitro in pancreatic cancer cell lines. Downregulation of MALAT1 reduced self-renewal-associated factors, such as SOX2, Bmi and Nanog.…”
Section: Metastasis-associated Lung Adenocarcinoma Transcript 1 (Malat1)mentioning
confidence: 99%
“…MALAT has been found to be highly overexpressed in several human malignancies and has been associated with tumor invasion and metastasis in various cancers. [78][79][80][81][82][83][84] Jiao et al 78 reported that MALAT1 could increase the proportion of pancreatic CSCs, maintain self-renewal capacity, decrease chemosensitivity to anticancer drugs and promote angiogenesis in vitro in pancreatic cancer cell lines. Downregulation of MALAT1 reduced self-renewal-associated factors, such as SOX2, Bmi and Nanog.…”
Section: Metastasis-associated Lung Adenocarcinoma Transcript 1 (Malat1)mentioning
confidence: 99%
“…Various lncRNAs, such as HOTTIP, MEG3, UCA1 and MALAT1, have been demonstrated to be involved in different carcinomas including MM [9]. MicroRNAs are critical members of non-coding RNAs (ncRNAs), which are 22 nucleotides in length.…”
Section: Introductionmentioning
confidence: 99%
“…We also found aberrant expression of 1,733 mRNAs in A549/PTX cells compared with the parental A549 cells. Various of the differentially expressed lncRNAs and mRNAs including, MALAT1, TUG1, HOTAIR, ABCB1 (MDR1) and Wnt6 have been previously reported in other chemoresistant cancers (23)(24)(25)(26)(27). Whether the molecular mechanisms of chemoresistance are the same as in the A549/PTX cells warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%